Mengembangkan E-Learning Pariwisata Budaya Pada Era 4.0 - I Gusti Agung Alit Suryawati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
This scientific work aims to discuss public access to e-learning at Udayana University and its development as a center for cultural tourism studies in Indonesia in Era 4.0. As a result of the qualitative study, research data were obtained through observation, interviews with 12 informants who managed and managed e-library users at Udayana University, Denpasar, as well as study documents related to the research topic. The collected data were analyzed descriptively-qualitatively. The results of the study show that to support the teaching and learning process, Udayana University has developed an e-learning system that is equipped with an adequate e-library. Part of the academic community within the University of Udayana has used the e-library developed by the University of Udayana to support their studies. Udayana University has the potential to become an e-Learning Center in the field of cultural tourism in the 4.0 era today. It was recommended, that Udayana University e-library management continue to disseminate the existence of e-learning through community services and continue to strengthen e-library by continuing to update and add and reference "cultural tourism" according to the challenges of the development of tourism in the 4.0 era.